О гидросиликатных и лиственитовых метасоматитах - Дерябин, Н.И. (Видавничий дім "Академперіодика" НАН України, 2007)
We consider the facies and the metasomatic zoning of hydrosilicate and leaflike metasomatites. Alkaline conditions of their formation are judged.